The Dynamics of Islamic Jurisprudence in The Eyes of Contemporary Muslims - Meirison Meirison; Husnul Fatarib; Desmadi Saharuddin (El-Mashlahah, 2022)
The emergence of sects and their diversity in Islam is caused by the differences in thought and visions of those who follow these sects. When the differences between the followers of these sects is limited to a mere difference of views on this or jurisprudential issue, it is a disagreement or an acceptable difference. Because there is more than one opinion on one jurisprudential issue, so whoever works with this opinion on the issue, his action is permissible. And, whoever works on the same issue with another thought, his movement is also acceptable, and this is from the capacity of Islam and its mercy to the nation. By examining several books related to the views of the ulama on the schools of thought, it has opened the way for us to verify. The article carried out a descriptive analysis approach and a comparative study of the opinions of scholars in different schools of thought and the fatwas issued by our official fatwa institutions. The article find the fanaticism of the sects is one of the causes of the nation's weakness. So, its unity was torn, and its humiliation intensified for the people. And that, they agree on what they agreed upon of the fixed principles, although various problems arise from time to time.